Information Management skills in Self-Directed Learning and Permanently - Pocevičienė, Rasa (Encontros da Licenciatura em Ciências e Tecnologias da Documentação e Informação, 2023)
Information Management skills such as knowledge about content management, ability to analyze and synthesize information, analytical ability to combine and organize complex information, problem-solving ability and etc. are very important not only in permanently changing world, labor market as well as preparing to active participation in them. The ever-increasing amount of information, the emergence of new channels for its transmission, and the increasing opportunities for the creation and dissemination of information (especially in the online space) pose challenges not only in quantitative terms. Even more important is the selection of information, the development of its criteria, the assessment of the quality of information, the creative application of the information in solving various problems, and so on. [...]